Dendroclimatologia de quatro espécies florestais nativas com potencial silvicultural e econômico - Munareto, Felipe Fortuna (2007)
An forest species that it presents annual tree-rings makes possible the recomposition of the last growth in way relatively fast, through the trunk analysis. In dendroecology studies, the annual tree-rings show possible relationships climategrowth and the occurrence of last disturbances. In that way, it is noticed the importance in studying the influence of the climatic factors in relation to the tree in any period of the year. Being used of that, it was evaluated as climatic variables influence in the growth of four native forest species: Luehea divaricata, Schefflera morototonii, Cedrela fissilis and Enterolobium contortisiliquum, with the objective of evaluating the behavior of those species, located in Campo de Instrução do Exército de Santa Maria (CISM), in Santa Maria - RS, regarding the diametric growth, determining the correlation among trees of same species, similarities in they growth, the climatic influence in the growth in diameter of the studied species. Temporary series of the monthly medium temperatures and monthly rainfall had been used from January, 1969 to December, 2000 originated by Santa Maria's meteorological station (RS). They had been sampled just dominant trees, whose sequences of increment of their transversal sections had been obtained through the graphic procedure LINTAB. The correlations had been calculated by SPSS 7.5 program, using the Pearson s correlation procedure. The sensibility of the growth answer due to possible environmental and climatic factors respectively, it had been calculated through sensitivities (Schweingruber, 1983). All of the correlations among the rays, traverse section, trees and species were significant with error probability level of 1%. The trees didn't present growth liberation and they were sensitive to the climatic signs. The united analysis of the nine studied trees indicates that the increase of rainfalls in April previous to growth period it is unfavorable, while in January and February the increase of rainfall benefits the tree s studied growth, as well as the increase in the temperature in May